Bioconversion of crude glycerol from waste cooking oils into hydrogen by sub-tropical mixed and pure cultures - Rodrigues, Caroline Varella [UNESP] (2018)
This study compared the biohydrogen generation by sub-tropical mixed and pure cultures from the crude glycerol from the biodiesel production using waste cooking oils (WCO). The crude glycerol was pretreated by pH adjustment. The mixed culture was obtained from a subtropical granular sludge of the UASB (Upflow Anaerobic Sludge Blanket) reactor used in the treatment of vinasse from sugarcane of ethanol and sugar industry. It was heat treated in order to inactivate hydrogen-consuming bacteria, which was identified by Illumina MiSeq Sequencing with a relative abundance of 97.96% Firmicutes Philum, 91.81% Clostridia Class and 91.81% Clostridiales Order. The pure culture was isolated from a sub-tropical granular sludge from UASB reactor of treating brewery wastewater and identified as Enterobacter sp. (KP893397). Two assays were carried in anaerobic batch reactors in order to verify the hydrogen production from crude glycerol bioconversion with: (I) mixed culture and (II) pure culture. The experiments were conducted at 37 °C, initial pH of 5.5 for assay I and 7.0 for assay II, with 20 g COD L−1 of crude glycerol. The crude glycerol consumption was 56.2% and 88.0% for the assay I and II, respectively. The hydrogen yields were 0.80 moL H2 mol−1 glycerol for the assay I and 0.13 moL H2 mol−1 glycerol for the assay II. Enterobacter sp. preferred the reductive metabolic route, generating 1460.0 mg L−1 of 1,3-propanediol, and it showed to be more sensitive in the presence of methanol from crude glycerol than mixed culture that preferred the oxidative metabolic route with biohydrogen generation. The mixed culture was more able to generate H2 than pure culture from the crude glycerol coming from the biodiesel production using WCO.